2010
DOI: 10.1007/s11192-009-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Web of Science with the Conference Proceedings Citation Indexes: the case of computer science

Abstract: In September 2008 Thomson Reuters added to the ISI Web of Science (WOS) the Conference Proceedings Citation Indexes for Science and for the Social Sciences and Humanities. This paper examines how this change affects the publication and citation counts of highly cited computer scientists. Computer science is a field where proceedings are a major publication venue. The results show that most of the highly cited publications of the sampled researchers are journal publications, but these highly cited items receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…For instance, comparing the 254 TRECVid papers which Scopus and Scholar both located in 2007, we found that 1/3 of the Scopus papers had located no citations at all, and Figure 1 shows the dramatic drop in citations per papers for both databases. Normally what matters are the documents that have been cited a large number of times, and it is interesting and important for the field to find out why, what they are about, who wrote them, and where they were published [1,9]. Thus, in general, more effort should be put into carefully cleaning and checking this data rather than the long tail of non-cited documents These highly cited documents can be analysed in detail.…”
Section: Conclusion On Data Accuracymentioning
confidence: 99%
“…For instance, comparing the 254 TRECVid papers which Scopus and Scholar both located in 2007, we found that 1/3 of the Scopus papers had located no citations at all, and Figure 1 shows the dramatic drop in citations per papers for both databases. Normally what matters are the documents that have been cited a large number of times, and it is interesting and important for the field to find out why, what they are about, who wrote them, and where they were published [1,9]. Thus, in general, more effort should be put into carefully cleaning and checking this data rather than the long tail of non-cited documents These highly cited documents can be analysed in detail.…”
Section: Conclusion On Data Accuracymentioning
confidence: 99%
“…Since WoS does not enable the science domain to be specified in a straightforward way, we were forced to limit ourselves to publications appearing in journals classified as computer science sources. The data collection we have chosen has an obvious limitation: it is biased towards computer scientists who prefer publishing their research in journals, although it is well known that computer science research is presented at conferences to a greater extent than other fields of science (Bar-Ilan, 2010;Franceschet, 2010;Wainer et al, 2011). On the other hand, computer science journal articles receive more citations on average than conference papers (Franceschet, 2010) and we can expect that with a growing pressure on the visibility of papers and a faster journal editorial process, both of which we have been witnessing in recent years, the need for publishing computer science research in journals will increase.…”
Section: Datamentioning
confidence: 99%
“…The research performance of global universities in computer science has been explored too [9]. Other investigations have been more concerned with the role of computer science conferences and their lower impact compared to journals [10][11][12][13] while some research has also been devoted to the study of the citedness of computer science journals [14,15]. Some works have been very specific and have inspected the evolution of the number of authors [16] or of the age of cited references [17] in computer science publications.…”
Section: Introductionmentioning
confidence: 99%